Comparison of the Rights and Obligations of Husband and Wife in the Compilation of Islamic Law and Indonesian Civil Law - Agus Salim; Sari Wulandari (Indonesian Journal of Islamic Law, 2023)
This research examines the psychological impact of divorce on children and the responsibilities of parents in providing emotional and psychological support according to Islamic family law. This research aims to compare the rights and obligations of husband and wife in the Compilation of Islamic Law (KHI) and the Civil Code (KUH Perdata) in Indonesia. Using literature study methods and a qualitative analysis approach, this research explores the similarities and differences in the regulation of the two legal systems and their implications for gender justice in husband and wife relationships. The results of the analysis show that both the KHI and the Civil Code place the husband as the head of the family and give the traditional role to the wife as housewife. However, this approach often reinforces unfair gender stereotypes. Data from the Central Statistics Agency (2022) shows an increase in women's participation in the workforce, while a study by UN Women (2018) shows that families that implement gender equality tend to be more harmonious. Therefore, legal reform is needed that is more responsive to changing social dynamics to achieve gender equality and justice in marriage in Indonesia.